Experimental investigation of the fatigue crack growth behavior in wire arc additively manufactured ER100S‐1 steel specimens. Issue 2 (26th October 2021) - Ermakova, Anna; Ganguly, Supriyo; Razavi, Javad; Berto, Filippo; Mehmanparast, Ali
Abstract: Wire arc additive manufacturing (WAAM) is an advanced fabrication technology for the rapid and efficient production of large‐scale engineering structures. In order to design WAAM components for a given loading condition, it is essential to characterize the mechanical and failure behavior of the parts. In this study, the performance of ER100S‐1 low carbon steel has been investigated by performing fatigue crack growth tests on compact tension specimens extracted from a WAAM built wall. The experimental results have been compared with the recommended trends in the BS7910 standard and with data available in the literature. Metallurgical investigations have been carried out to explore the microstructural effects on the fatigue behavior of the WAAM built components. The specimen location and orientation effects were comprehensively examined, and the results are discussed in terms of the influence of macroscopic and microscopic deformation on the overall response of the WAAM built components under fatigue loading conditions.